Energy Recovery Using Ratchet Mechanism: An Experimental Study. (August 2017) - Younas, Tanzila; Saadat, Muhammad; Hussain, Imran; Rashied, Zubair
Abstract: Renewable energy is widely used term in today's world as it is pollution free and ecofriendly and people are focusing towards alternative sources of energy which is cost effective and can be used for a long period of time. The proposed technique discussed in this paper as a solution is based on ratchet mechanism designed for speed breakers. The load passes over speed breaker transmit Potential energy onto rack and pinion arrangement. Designed mechanism depends on the flow of traffic to generate electricity which is the loop hole for transmitting load to rack and pinion. The back and forth motion is responsible for the conversion of Potential Energy into Kinetic Energy and acquiring Kinetic energy is further utilize by converting it into Electrical Energy using dynamo generator stored in power bank. AC voltage required for street lights and Traffic system is acquired using inverter. This mechanism can be installed where flow of traffic is high and higher the number of vehicles passes over this mechanism results maximum voltage.